Ensino informatizado de leitura e escrita para alunos dos anos iniciais do ensino fundamental na abordagem da resposta à intervenção no contexto da pandemia do Covid-19 - Muto, Jéssica Harume Dias (Universidade Federal de São Carlos, 2021)
The Multi-tier Intervention Response (RTI) model aims to intervene early with children who are at risk (or difficulty) in acquiring academic skills. Thus, the model presents a direction in relation to the service proposal to work on the students' needs, demonstrating a preventive model to reduce academic difficulties, specifically for reading and writing in this study. Considering the promising results found with the use of an individualized and computerized reading and writing program (Learning to Read and Write in Small Steps - ALEPP), the present study aimed to evaluate the effects of this program, combined with the RTI model, on students entering elementary school at a public regular education institution. Due to the circumstances of the suspension of classes due to the Covid-19 pandemic, this research was divided into two studies. Study 1 partially used ALEPP's Module 1, combined with the multi-tier model of Response to Intervention, as a preventive measure against difficulties related to reading and writing learning by students entering elementary school with face-to-face application. In this study, we sought to monitor the performance of students from two classes of the 1st school year in large-scale assessments of reading skills. A quasi-experimental design with non-random distribution of participants was used, involving direct manipulation and control of variables of interest. Initially, pre-test data were collected through government assessment (PMAlfa) and a functional assessment measure instrument (FAM) of academic areas answered by the professor. Based on the multi-tier service, participants from each of the two classes were selected to carry out the reading and writing teaching program (tier 2 and 3 of the RTI). At the end of the school year, the same assessments (PMAlfa and FAM) were applied in order to verify possible effects of the proposed intervention with students with difficulties in reading and writing. The results showed that nine out of twelve students showed an increase in performance in reading and writing, one participant showed an increase in reading performance, one participant showed no increase in performance in the skills assessed, and one participant did not perform a monitoring assessment of their learning. In general, the assessments used to evaluate and direct participants to the tieres showed that the screening of students with signs of difficulties in traditional classroom teaching processes corresponds to an alarm of the need for intervention beyond the usual procedures of classroom. The data suggest that the RTI model is favorable for referring students to group and/or individual interventions. Study 2 used ALEPP Modules 1 and 2 with online application, with four students selected through the multi-tier model in Study 1, in the face-to-face context before the Covid-19 pandemic. Data collection with one of the participants, diagnosed with ASD, had the participation of the mother. The results showed that children benefited from exposure to the teaching program during the suspension of in-person classes, proving to be a promising resource for individualized online care.
Computerized teaching of reading and writing for students in the early years of elementary school in the approach to the response to Intervention in the context of the Covid-19 pandemic
Keywords: Leitura e escrita; Ensino fundamental; Modelo multicamadas; Programa informatizado; Covid-19; Reading and writing; Elementary school; Multi-tier model; Computerized program; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::PSICOLOGIA